Recent changes to the regulatory framework for the private capital market - Ivanov, Vladimir I. (Journal of Corporate Finance, 2023)
The study reviews key regulatory events in the private offerings market during the period 2005–2020. One goal of this review is to help researchers identify and better understand these regulatory changes, and how they affect capital raising and investing in this market. Hopefully, some of them also could be used as exogenous shocks in future research. Another goal is to encourage researchers to study more closely some of the recent regulatory changes and nudge them to explore interesting issues in the private offerings area. Recent studies that have studied some of these regulatory events are reviewed as well.